2008
DOI: 10.1111/j.1863-2378.2008.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Infection among Domestic Animals in Eastern China

Abstract: Hepatitis E virus (HEV) is a zoonotic pathogen of which several species of animal were reported as reservoirs. Antibodies to HEV and HEV RNA have been detected in some Chinese population and swine groups but few other domestic animals. In this study, to investigate the HEV prevalence, we tested sera from 788 pigs, 100 cows, 50 goats, 49 horses, 101 pet dogs, 105 chickens, 47 duck and 45 pigeons in eastern China for anti-HEV immunoglobulin G (IgG). We also tested 50% of the swine sera, all of sera from the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
97
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 29 publications
7
97
1
1
Order By: Relevance
“…It has been reported that anti-HEV prevalence among horses in Egypt and eastern China is 13.0% and 16.6%, respectively, and partial HEV genomes were also identified in horses from these two areas. 23,24 However, no more studies could independently confirm it, and our study failed to amplify HEV RNA from donkeys and horses in Xinjiang, although similar anti-HEV prevalence rates were found in donkeys (13.77%) and horses (11.00%). Consequently, the occasional reports of isolation HEV RNA from horses seem to represent laboratory contamination rather than genuine infection.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…It has been reported that anti-HEV prevalence among horses in Egypt and eastern China is 13.0% and 16.6%, respectively, and partial HEV genomes were also identified in horses from these two areas. 23,24 However, no more studies could independently confirm it, and our study failed to amplify HEV RNA from donkeys and horses in Xinjiang, although similar anti-HEV prevalence rates were found in donkeys (13.77%) and horses (11.00%). Consequently, the occasional reports of isolation HEV RNA from horses seem to represent laboratory contamination rather than genuine infection.…”
Section: Discussionmentioning
confidence: 70%
“…Cows showed the lowest positive rate (6.50%) for anti-HEV among domestic herbivorous animals with a rate similar to the 6.00% reported in eastern China. 23 This suggests that cows might be less susceptible to HEV than horses, donkeys, and goats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include rodents (1,10,12,14,25,27,28,51,60,64), cats (31,35,41,43), dogs (1,35,41,60,71), horses (14,16,49,71), donkeys (14), goats (14,16,45,52,71), sheep (5,45,61,66,68), cattle (1,5,14,21,60,63,71), rabbits (16,17), nonhuman primates (46,67), mongooses (34,42), chickens (18,23,52,60,71), ducks …”
mentioning
confidence: 99%